Solar thermoelectric cooling technology applied to transport of vaccines in isolated communities - Milón Guzmán, Juan José (2020)
Solar thermoelectric cooling technology applied to transport ofA thermoelectric cooling system supplied by photovoltaic solar energy was built and evaluated with different thermal loads. The thermoelectric cooling module consumes 70 W, it is supplied by a photovoltaic system of 90 W and 40 Ah battery. The voltage and electrical current in each component (panels, battery, and electric charge) has been measured. The tests were performed with different thermal loads placed in glass containers used for vaccines. To analyze the cooling and preservation process, the experiments were started at room temperature. The results show that the thermoelectric cooling system works for small thermal loads, and it could be applied to transport vaccines in isolated areas where people carry medicines in small containers that do not maintain the temperature necessary for the conservation of vaccines. vaccines in isolated communities.